STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PEMBERDAYAAN MASYARAKAT KELURAHAN (PPMK) DI KOTA BANDAR LAMPUNG - Damara, Cherrya; Nikmatullah, Dewangga; Nurmayasari, Indah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research aimed to determine the effectiveness of empowerment strategies PPMK in Bandar Lampung through revolving fund programs and computer training and to determine the benefits of revolving fund programs and computer training through PPMK in Bandar Lampung. This research was conducted in May until August 2014. Primary and secondary data were collected in this reserch. The sampling used purposive sampling with 49 research subjects. The data was analyzed by qualitative, and collected by observation, interview, documentation, and Focus Group Discussion. The results showed that strategies of Society Empowerment (PPMK) through computer training and revolving funds was effective, since the implementation of the carried out activities were suitable with the general guidelines PPMK such as, Utilization of funds for productive business were 80%, the amount of funds that had been appropriate for running the business were 71.43%, for the computer trainings the training result used by participants to get a job was 79.58%, the materials application of Microsoft Word and Microsoft Exel that had given appropriately amounting to 67.86 %. The benefit for the participants after the revolving fund was the participants could use the received funds to increase business capital, to develop and to promote the business, then to fulfill the household necessity whereas the benefits for the participants after the computer program was getting knowledge, getting certificates that may use for applying jobs and for opening new computer businesses. Key words: effectiveness, PPMK, society empowerment